ACAT1/SOAT1 maintains adipogenic ability in preadipocytes by regulating cholesterol homeostasis - Qing Liu; Xiaolin Wu; Wei Duan; Xiaohan Pan; Martin Wabitsch; Ming Lu; Jing Li; Li-Hao Huang; Zhangsen Zhou; Yuyan Zhu (Journal of Lipid Research)
Maintaining cholesterol homeostasis is critical for preserving adipocyte function during the progression of obesity. Despite this, the regulatory role of cholesterol esterification in governing adipocyte expandability has been understudied. Acyl-coenzyme A (CoA):cholesterol acyltransferase/Sterol O-acyltransferase 1 (ACAT1/SOAT1) is the dominant enzyme to synthesize cholesteryl ester in most tissues. Our previous study demonstrated that knockdown of either ACAT1 or ACAT2 impaired adipogenesis. However, the underlying mechanism of how ACAT1 mediates adipogenesis remains unclear. Here, we reported that ACAT1 is the dominant isoform in white adipose tissue of both humans and mice, and knocking out ACAT1 reduced fat mass in mice. Furthermore, ACAT1-deficiency inhibited the early stage of adipogenesis via attenuating PPARγ pathway. Mechanistically, ACAT1 deficiency inhibited SREBP2-mediated cholesterol uptake and thus reduced intracellular and plasma membrane cholesterol levels during adipogenesis. Replenishing cholesterol could rescue adipogenic master gene–Pparγ′s—transcription in ACAT1-deficient cells during adipogenesis. Finally, overexpression of catalytically functional ACAT1, not the catalytic-dead ACAT1, rescued cholesterol levels and efficiently rescued the transcription of PPARγ as well as the adipogenesis in ACAT1-deficient preadipocytes. In summary, our study revealed the indispensable role of ACAT1 in adipogenesis via regulating intracellular cholesterol homeostasis.